Risk Assessment for Speedboat Tourism in Raja Ampat Using the Swiss Cheese Model (SCM) - Arif, Antoni; Widarbowo, Dodik; Haryanto, Dwi; Gumelar, Fajar; Filemon, Filemon (Institut Teknologi Sepuluh Nopember, 2025)
The waters of Raja Ampat in Papua are one of the world's top maritime tourism destinations, attracting over 30,000 tourists annually since 2020. However, the challenging geographical conditions, such as shallow coral reefs, strong sea currents, and busy speedboat traffic, significantly increase the risk of maritime accidents. According to the National Disaster Management Agency (BNPB), from 2012 to 2024, six incidents in the area caused serious accidents, including vessel damage and injuries. This study aims to analyze the risks of tourist speedboat accidents in Raja Ampat using three complementary risk assessment methods: the Swiss Cheese Model (SCM), interviews, and questionnaires. The Swiss Cheese Model identifies gaps in several layers, such as Environment and Weather, Vessel and Safety Equipment, Skills and Competence of Operators, and Tourism Safety Management and Regulations. The analysis shows that the skills and competence of boat operators are significant weaknesses in accident cases, and it recommends that boat operators in Raja Ampat participate in SCRB (Survival Craft and Rescue Boat) training and certification programs